KEBIJAKAN PENGURANGAN RISIKO BENCANA COVID-19: PENGALAMAN SEKOLAH TUMBUH - Dwitya Sobat Ady Dharma (usat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2020)
All educational institutions, both private and public, have a role and responsibility to continue to provide quality education. In the context of policy, educational institutions must be able to produce strategic policies that are not only student-centered, but also able to facilitate school members to carry out their functions optimally. This study focuses on policies taken on COVID-19 disaster risk reduction (PRB) in Yogyakarta Tumbuh Schools (SD Tumbuh 1, SD Tumbuh 2, SD Tumbuh 3, SD Tumbuh 4, SMP Tumbuh, and Tumbuh High School). This study used qualitative methods with a literature and empirical approach. The data is obtained from the COVID-19 disaster emergency response policy formulated by the School Principal, HRM, and phenomena that occur in schools. The data used are in the form of circular letters as policy products, and various documents. The results showed that the DRR policies in Growing Schools applied humanist principles that were able to accommodate the needs of school residents (students, teachers, and staff). Policy implementation is carried out in a systematic flow so that it is easily understood by school residents and is made by prioritizing the deliberations of the leaders.